A Center-Fed Beam-Steerable Series Antenna Array With a Wide Matching Bandwidth - Sungeun Kim; Haegwon Park; Byung-Wook Min (IEEE Open Journal of Antennas and Propagation, 2024)
In this paper, a center-fed beam-steerable series antenna array is presented that has both a wide matching bandwidth and easy control. The proposed matched feeding network for the series array is composed of impedance transformers and voltage-controlled phase shifters, and has a fractional bandwidth of 74%. The phase shifters are designed in a reflection-type configuration to minimize loss and reduce size. The 3-way power divider used in the proposed center-fed series array enable beam steering with only two control voltages for phase shifters. To demonstrate the beam-scanning capabilities of the proposed antenna array, the proposed feeding network was combined with angled-dipole antennas. The proposed antenna array has a scan angle of ±60° at 3.5 GHz, with a gain varying from 8.9 to 10.4 dBi. It also has a broadband matching bandwidth of 20% and a low beam-squint of ±2° in the 0.2 GHz band centered at 3.5 GHz.